Networked architectures of crime prevention: community mobilization in Manitoba - Gorkoff, Kelly (Canadian journal of criminology and criminal justice, 2022)
Crime prevention programs in Canada have increasingly adopted community mobilization frameworks – a process in which individuals, groups, and organizations in a community come together to address particular social issues associated with individual risk, health and safety, crime prevention, and community development. These initiatives intend to address systemic issues that are strongly correlated with criminal activity and with community safety and well-being. Twelve community mobilization (CM) initiatives have been established in Manitoba. CM is often considered an innovative way to deal with high-risk individuals who are best served by an approach that activates communities to act on their behalf and, by doing so, increases community safety. CM is also considered a networked form of crime control that activates groups not normally involved with crime control. Although intending to mobilize communities to act, some of these programs have been critiqued as being state-centric and promoting a police agenda. We have found preliminary evidence that Manitoban initiatives have avoided these problems and retained autonomy and local governance in their design and operation. Using the theoretical concept of nodal networks (organizational sites that bring together institutions to shape a flow of events), we argue that models of CM in Manitoba have maintained local leadership and resisted standardization, which gives them the potential to meet the original goals of CM: to co-produce community-grounded definitions and practices of public safety. We introduce indicators to verify these nodal networks and discuss the possibilities for reimagining public safety.